The Literary and Recent Scientific History of the Earworm: A Review and Theoretical Framework. Issue 1 (3rd April 2018) - Beaman, C. Philip
ABSTRACT: The phenomenon of the earworm – the song that replays within the head and will not go away – is reviewed. Earworms have been of interest to commentators for some time, as demonstrated by their appearance in popular culture. Despite this popular interest, and the speculative links sometimes drawn between earworms and clinical conditions such as Obsessive Compulsive Disorder, they have attracted empirical investigation from music psychologists and auditory cognition researchers only recently. A number of implicit assumptions about the phenomenon are evident within the empirical literature but no theoretical rationale for the earworm has been put forward explicitly. Historical and literary accounts of music being "stuck in the head" are reviewed for their accuracy relative to more recent empirical findings about earworms. A short account, based upon existing knowledge and theorizing in cognitive psychology, is then sketched out as a guiding framework for future empirical work. Some predictions of this "business-as-usual" theory of earworms are shown to be supported by more recent data.